TOURIST-RECREATIONAL ZONES - MANAGEMENT MECHANISM OF THE FORM, AND THE NEW YEAR ABROAD EXPERIENCE (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
This article in the tourist-recreational zo'nalarni management mechanisms of international experience, in particular, developed countries have implemented public-private partnership models, tax benefits and the organizational-legal basis of the analysis is. The article within the framework of the usa, France, Turkey and Spain, like countries in the area of successful strategies bodice out of, of them Uzbekistan conditions of use